Reversible Improvement of Arterial Stenosis and Wall Thickness in Takayasu Arteritis Through Treatment With Tocilizumab - Shinichi Nogi; Yusuke Yano; Kako Kodama; Hirotaka Tsuno; Hideki Ogihara; Masahiro Kawakami; Tomoko Ohmori; Shinji Sato; Toshihiro Matsui (Annals of Internal Medicine: Clinical Cases)
Early diagnosis and initiation of treatment in Takayasu arteritis (TA) is important to prevent irreversible arterial changes. A 39-year-old female was diagnosed with active TA. Subcutaneous administration of tocilizumab (162 mg/week) was initiated in combination with prednisolone (30 mg/d). After 21 months, the carotid arterial stenosis and wall thickness had normalized with only slight plaque on echocardiography. After 23 months, computed tomography showed normalization of the overall aortic stenosis and wall thickness. The prednisolone dosage could be reduced to 2 mg/d without relapse for >2 years. Early combination treatment of TA with tocilizumab prevented and normalized vascular stenosis and wall thickness.